Screen time and metabolic syndrome among expatriate adolescents in the United Arab Emirates. Issue 4 (July 2019) - Khan, Moien AB; Shah, Syed M.; Shehab, Abdullah; Ghosal, Samit; Muhairi, Shamma J.; Al-Rifai, Rami H.; Al Maskari, Fatima; Alkaabi, Juma; Nauman, Javaid
Abstract: Background: Both screen time and metabolic syndrome (MetS) are associated with health outcomes. However, limited data exist on the association between screen time and MetS among expatriate adolescents living in United Arab Emirates (UAE). Methods: We conducted a cross-sectional school-based study on 473 expatriate adolescents (47% girls) aged 12–18 years in Al-Ain district of Abu Dhabi Emirates in the UAE. Data was collected with the expertise of trained nurses & IDF criteria was used to define MetS. Information on screen time (computer, television, and video game use combined) during a regular day was self-reported, and divided into two categories: <2, or ≥2 h per day. Using logistic regression analyses, adjusted odds ratios (OR) and 95% confidence intervals (CI) were estimated for the association between screen time and MetS. Results: A high proportion of adolescents (75.3%) spent ≥2 h daily on screen. The prevalence of MetS was 8.5% in those with <2 h per day of screen time compared with 13.5% in those who reported ≥2 h per day. There was a graded positive association between screen time and MetS ( P -trend = 0.01). Each hour increase in screen time was associated with 21% (OR, 1.21; 95% CI, 1.08–1.35) greater likelihood of having MetS. The adjusted OR value associated with ≥2 h of daily screen time was 2.20 (95% CI, 1.04–4.67), compared with adolescents who spent less than 2 h of daily screen time. Conclusion: Higher screen time by expatriate adolescents was associated with increased likelihood of having MetS.